Local content in oil and gas law : a practical guide from design to implementation - Pereira, Eduardo G.; Olawuyi, Damilola S. 1983-; Ingelson, Allan, 1958- (Routledge research in energy law and regulation, 2026)
This book explores the development and effective implementation of local content policies in the global petroleum industry, providing a comprehensive overview of the foundations and drivers of local content in oil and gas. Against the backdrop of a growing focus on sustainable development and economic diversification, this comprehensive book addresses the challenges and opportunities of increasing local participation in the oil and gas sector. The book navigates complex topics such as regulatory frameworks, stakeholder engagement, indigenous rights, capacity building, and the intersection of local content with sustainability and gender equality. Through detailed case studies and global examples, the book identifies obstacles such as funding, resource curse, corruption, transparency, strategic planning and adherence to international standards and regulations, while also exploring the critical role of local content in the energy transition and circular economy. The book not only enriches academic discourse but also serves as a pragmatic guide to aligning local development goals with global industry demands. The book links national development aspirations with global industrial realities, offering a practical guide to successful local content policy development and execution. Offering a practical roadmap for policymakers, industry leaders, and scholars to design, implement, and monitor impactful local content strategies, the book will be of interest to researchers in oil and gas law and policy.